2023
DOI: 10.1186/s13018-023-04149-x
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve of tibial cortex transverse transport: a cumulative sum analysis

Jun-Peng Liu,
Xing-Chen Yao,
Zi-Yu Xu
et al.

Abstract: Objective This study aimed to describe the learning curve of surgeons performing tibial cortex transverse transport (TTT) and explore its safety and effectiveness during the initial stages of surgeon’s learning. Methods The clinical data of patients with diabetic foot ulcers classified as Wagner grade ≥ 2, who underwent TTT at our hospital from January 2020 to July 2021, were included in this retrospective analysis. The same physician performed all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Matsuyama et al found that the distraction area exhibited more than three times greater ratio of average blood vessel volume than the intact contralateral tibiae [ 31 ], which was consistent with our results that TTT could significantly increase dorsal foot blood flow of patients at the 4th weeks after TTT. For better application of TTT in clinical practice, Liu et al described the learning curve of surgeons performing TTT, demonstrating surgeons can master TTT after completing approximately 20 procedures and yielded almost consistent clinical outcomes in the initial implementation stages [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matsuyama et al found that the distraction area exhibited more than three times greater ratio of average blood vessel volume than the intact contralateral tibiae [ 31 ], which was consistent with our results that TTT could significantly increase dorsal foot blood flow of patients at the 4th weeks after TTT. For better application of TTT in clinical practice, Liu et al described the learning curve of surgeons performing TTT, demonstrating surgeons can master TTT after completing approximately 20 procedures and yielded almost consistent clinical outcomes in the initial implementation stages [ 32 ].…”
Section: Discussionmentioning
confidence: 99%